(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This experience report exemplifies common elements to the trajectories of emergence and evolution of numerous museums founded by puppeteers. In it, life history, group poetics and patrimonial mediations confirm the paths for the genesis of puppet collections, bringing the concept of pragmatic conservation as a result of the puppet collecting practice. Its procedures address specific problems of the patrimonialization of the puppet and the transmission of memory, such as: the adequacy of the exhibition spaces, lighting, forms of storage, pest control; as well as conceptual approaches for the unique decisions on the scope and nature of piece-by-piece restoration interventions. Finally, and no less pressing, the report reveals the conflicting relationship with the future of personal collections, in the search for strategies and continuity solutions for the maintenance of the puppeteer heritage.